Malicious objects, anger management, and the question of modern literature - Kreienbrock, Jörg, 1969- (Fordham University Press, 2013)
Why do humans get angry with objects? Why is it that a malfunctioning computer, a broken tool, or a fallen glass causes an outbreak of fury? How is it possible to speak of an inanimate object's recalcitrance, obstinacy, or even malice? When things assume a will of their own and seem to act out against human desires and wishes rather than disappear into automatic, unconscious functionality, the breakdown is experienced not as something neutral but affectively--as rage or as outbursts of laughter. Such emotions are always psychosocial: public, rhetorically performed, and therefore irreducible to a "private" feeling. By investigating the minutest details of life among dysfunctional household items through the discourses of philosophy and science, as well as in literary works by Laurence Sterne, Jean Paul, Friedrich Theodor Vischer, and Heimito von Doderer, Kreienbrock reconsiders the modern bourgeois poetics that render things the way we know and suffer them